Assessment of acute and chronic pain in canine internal medicine—what is missing in our diagnostic toolbox? - Sander, Annina N.; Storz, Sarah; Xenoulis, Panagiotis G.; Heilmann, Romy M. (Frontiers in Veterinary Science, 2025)
Perceiving pain is a protective mechanism among all animal species. It involves sensing pain and experiencing the associated discomfort, aversion, and negative emotions. These aspects are particularly complex and potentially impossible to quantify as a multidimensional and subjective experience. Pain can be communicated in various ways. However, the inability to verbally communicate this experience remains a challenge to assess and quantify pain in dogs, as there is no gold standard. Species- and animal-specific factors (e.g., age, breed, clinical condition, or anxiety) also need to be considered. Several pain scales have been established in veterinary medicine to improve analgesic, medical, and/or surgical treatment and provide additional prognostic and/or diagnostic information. These scales focus on assessing behavior and objective physiological parameters (e.g., heart rate, systemic blood pressure, mydriasis), which are not specific and can be affected by large inter-individual variation. Addressing this challenge in canine acute and chronic pain management requires accurate and effective pain scoring systems that work reliably with the underlying condition. Particularly for internal medicine conditions, more work is needed in the future, as there are no specific tools available that might improve diagnosis and treatment. This article provides a brief overview of the current knowledge about acute and chronic pain assessment in dogs, available pain scales, which are based on subjective assessment, and the limitations and challenges of using these tools in clinical practice. It offers perspectives for novel avenues and future applications for clinical pain scales and individualized pain assessment in canine internal medicine.